Circular economy versus planetary limits: a Slovak forestry sector case study. Issue 6 (18th December 2020) - Beckmann, Andreas; Sivarajah, Uthayasankar; Irani, Zahir
Abstract : Purpose: Circular economy is presented as an approach to economic growth that is in line with sustainable development. However, the recent literature has highlighted the limits of the concept in terms of environmental sustainability. The study examines the relationship between circular economy and conservation of ecosystems, using a case study on the implications of a circular economy for Slovak forests and forest sector. Design/methodology/approach: This study adopts a qualitative methodology through a focused review of the relevant literature on circular economy and sustainable development and primary data gathered through semi-structured interviews with 15 experts and practitioners in the forest sector, forest conservation and circular economy context, both from within as well as outside of Slovakia. Findings: The study finds that the forestry sector has an important role to play in a shift to a circular economy in Slovakia, with significant opportunities for improved efficiency as well as substitution of wood for non-renewable resources. There is also growing potential for ecosystem stewardship and restoration. However, the increased application of biomass could crowd out other needs, including for biodiversity. Safeguarding these services depends ultimately on good governance. Originality/value: The study highlights that circular economy taken in a narrow focus on resource efficiency is insufficient to ensure environmental sustainability but rather needs to be set within the broader environmental and social context.